Sex-specific and age-specific characteristics of body composition and its effect on bone mineral density in adults in southern China: a cross-sectional study - Hao Xu; Jian Gong; Zeyu Xiao; Zhiqiang Tan; Jingjie Shang; Yong Cheng; Yongjin Tang; Bin Guo (BMJ Open)
Objectives This study was an attempt to investigate the variation trend of body composition with ageing and explore the association between regional body composition and bone mineral density (BMD).Design Cross-sectional study.Setting and participants A total of 5749 healthy adults aged 20–95 years was recruited from 2004 to 2017.Primary outcome measures Whole-body lean mass (LM), fat mass (FM), android FM, gynoid FM, appendicular lean mass (ALM) and BMD in the lumbar spine, femoral neck and total hip were obtained by dual-energy X-ray absorptiometry (DXA). The android/gynoid fat mass ratio (A/G FMR) based on DXA scan was calculated as an indicator of adipose distribution. Pearson correlation and multiple linear regression analyses were used to determine the associations between body composition, adipose distribution, and BMD of each skeletal site.Results Whole-body FM, percentage of whole-body FM, Android FM and A/G FMR consistently increased with age in both genders, especially in women, and ALM began to decrease in the fifth decade for both men and women. In multivariable linear regression models with age, body mass index, A/G FMR and ALM as predictor variables, ALM was associated with the most BMD variance of all skeletal sites in men (standard β ranged from 0.207 to 0.405, p<0.001), although not the largest but still a positive predictor of BMD in women (standard β ranged from 0.074 to 0.186, p<0.05). A/G FMR was an inverse predictor of BMD at all skeletal sites for women (standard β ranged from −249 to −0.052, p<0.01) but not in men.Conclusions In this large cohort of Chinese adults, ALM had a strong positive association with BMD in both genders. A/G FMR as an indicator of central adipose accumulation was inversely associated with BMD in women but not in men.